Measurement of the B0 production cross section in pp collisions at √s=7TeV - Chatrchyan, S. (2011)
Measurements of the differential production cross sections dσ/dpTB and dσ/dyB for B0 mesons produced in pp collisions at √s=7TeV are presented. The data set used was collected by the CMS experiment at the LHC and corresponds to an integrated luminosity of 40pb-1. The production cross section is measured from B0 meson decays reconstructed in the exclusive final state J/ψKS0, with the subsequent decays J/ψ→μ +μ- and KS0→π+π-. The total cross section for pTB>5GeV and <2.2 is measured to be 33.2±2.5±3.5μb, where the first uncertainty is statistical and the second is systematic. © 2011 American Physical Society.